Less is More. Geschiedenis in het Rijksmuseum - Janssen, Geert H. (BMGN - Low Countries Historical Review, 2014)
Less is More: History at the RijksmuseumThe central idea behind the newly refurbished Rijksmuseum is to evoke ‘a sense of time, and a sense of beauty’. This prompts the question: what sense of time, and whose sense of beauty has the museum visualised? In what ways, moreover, can public institutions offer visitors a balanced ‘sense of the past’ when ‘beauty’ has served as the main criterion for selecting the objects on display? This essay addresses these questions by exploring the celebrated Dutch Golden Age collections of the Rijksmuseum.De nieuwe inrichting van het Rijksmuseum heeft als doelstelling ‘een besef van tijd op te roepen en een gevoel voor schoonheid’. Deze ambitie roept de vraag op welk besef van tijd en wiens gevoel van schoonheid worden gevisualiseerd in het museum. Op welke manieren kan een publieke instelling bovendien een evenwichtig ‘historisch besef’ oproepen wanneer ‘gevoel voor schoonheid’ de maatstaf is geweest voor wat wel en wat niet op zaal mag komen te hangen? In dit essay worden deze vragen besproken aan de hand van de veelgeroemde Gouden Eeuw-collecties van het Rijksmuseum.